limx→1 x8−2x+1×4−2x+1 equals

limx1x82x+1x42x+1 equals

  1. A

    3

  2. B

    0

  3. C

    -3

  4. D

    1

    Register to Get Free Mock Test and Study Material

    +91

    Verify OTP Code (required)

    I agree to the terms and conditions and privacy policy.

    Solution:

    We have, 

    limx1x82x+1x42x+1=limx1(x1)x7+x6+x5+x4+x3+x2+x1(x1)x3+x2+x1=limx1x7+x6+x5+x4+x3+x2+x1x3+x2+x1=62=3

    Chat on WhatsApp Call Infinity Learn

      Register to Get Free Mock Test and Study Material

      +91

      Verify OTP Code (required)

      I agree to the terms and conditions and privacy policy.